538 Long-term trajectories and predictors of disability in children surviving serious injury. (20th November 2022) - Ameratunga, Shanthi; Harrison, James E; Cameron, Peter; Ponsford, Jennie; Reeder, Sandra; Lyons, Ronan A; Teague, Warwick J; Nunn, Andrew; Gabbe, Belinda J
Abstract : Background: With improvements in injury control and advanced trauma care, increasing proportions of children survive major trauma, but population-based data on their long-term health and disability are scant. We investigated these outcomes in the five years following serious childhood injury in Victoria, Australia. Methods: Using the Victorian State Trauma Registry, this population-based prospective cohort study identified children (<18 years) admitted for major trauma over a 12-month period. Their functional recovery (KOSCHI or Glasgow Outcome Scale-Extended) and health-related quality of life (PedsQL) were assessed at 6, 12, 24, 36, 48 and 60-months post-injury. Multivariable regression models investigated factors associated with outcomes. Results: Of the 186 participants, 71% were retained to 60 months post-injury. Participants' functional status improved throughout the follow-up period but their psychosocial health remained low compared with their physical recovery. Even at five years post-injury, only 39% had fully recovered while 39% experienced moderate to severe disability. Factors associated with adverse outcomes included older age at injury, female sex, socio-economic disadvantage, remote/regional (cf. urban) residence, pre-existing comorbidities, and injuries deemed compensable, intentional, or involving head trauma. Conclusion: A high proportion (39%) of children surviving serious injury experience moderate to severe disability even five-years post-injury and their psychosocial recovery substantially lags improvements in physical function. Adverse outcomes are inequitably distributed by factors identifiable early in the course. Learning Outcome: The prolonged duration of disability following major childhood trauma highlights the need to strengthen injury control systems across the continuum of care, from prevention to equity focused post-trauma care and support.